Consequences of Poverty on Economic Decision-Making: Assessing the Verisimilitude of the Cognitive Mechanism - Adamkovič, Matúš (Frontiers in Psychology, 2020)
The paper aims to assess the verisimilitude of the hypothesized model of poverty perpetuation which links socioeconomic situation and economic preferences via cognitive load, executive functions and intuitive/deliberative decision-making styles. In order to test the model against the data, three studies (exploratory, confirmatory, and replication) were conducted with a total sample size of 1182 participants. The results showed that neither the proposed model as a whole found the required support in the data nor the consequent, theoretically justifiable, respecifications improved its fit so that it could be deemed acceptable. Simultaneously, the dyadic relationships between the variables were mainly found to be weak. The sensitivity analysis revealed that the majority of the observed estimates varied substantively depending on the arbitrary analytic decisions of the researcher. In summary, the hypothesized cognitive mechanism does not explain what economic decision-making depends on nor why people fall into poverty traps. The paper discusses several plausible sources of the negative findings and possible directions for future research are suggested.